(3GdaJGhi GdNGUjIs - (3YeQ Hf YHO GdYRjR Hf YeQ Hf eGRI, MSGe GdOjf CHh eMeO, GdUOQ GdTgjO , J (B536 (3g` s
(3ChdgG (B:s
(3cJGH GdHjhY s
(3BNQgG (B:s
(3eSCdI GdhUjI s
(3GdfSNI HgG MhGTs
(3fSNI KGfjIs
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B51 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B7 - (3U (B291s
Keywords: (3Gdabg GdMfajs